Clinical Patterns, Comorbidities and Stressors in Dissociative Disorders: A Hospital-Based Cross-Sectional Study - Bagban, Mohammad Ainuddin; Belbase, Mohan; Adhikari, Prabidhi (Journal of Nepalgunj Medical College, 2025)
Introduction: Dissociative disorders are characterised by disruptions in memory, consciousness, identity and perception of the self and environment. The high rate of comorbidity complicates diagnosis, emphasising the need for a comprehensive evaluation. Psychosocial stressors play a pivotal role in the onset and exacerbation of the disorder. Despite their high prevalence, there is a lack of systematic research on their clinical patterns, comorbidities, and psychosocial stressors. Most existing literature focuses on case studies or small-scale investigations. A detailed exploration of these aspects of the disorder facilitates early identification and management, ultimately enhancing patient outcomes. Aims: To analyse the clinical presentations, comorbid psychiatric conditions, and psychosocial stressors in dissociative disorders. Methods: A descriptive cross-sectional study was conducted from April 2025 to June 2025 at the Psychiatry Department of Nepalgunj Medical College among 50 patients aged 18-60 years, diagnosed with dissociative disorders, enrolled by convenience sampling. Unco-operative patients, those with severe psychiatric/medical illnesses, or cognitive disorders, were excluded. Sociodemographic and clinical data were recorded using a semi-structured proforma. Results: The majority of patients (88%) were from the age group 16 to 35, female (86%), married (60%), residing in a rural area (62%), belonging to nuclear families (70%) with lower middle-economic status (40%) and middle school education (32%) and anxiety disorder as a comorbidity. The most common clinical presentation was non-epileptic seizures, with the commonest stressor being family conflict. Conclusion: Our findings emphasis the need for family-based intervention as well as early psychosocial intervention and mental health support targeting these vulnerable groups